Arbuckle festival - Arbuckle, Roscoe, 1887-1933.; Keaton, Buster, 1895-1966.; Keystone Film Company; A-1 Video; Festival Films (Michigan City, IN : [released by] A-1 Video ; Minneapolis, MN : [distributed by] Festival Films, 1980)
Collection of four short silent films starring Fatty Arbuckle. Buster Keaton co-stars in Coney Island.
Fatty's faithful Fido (1915) -- Fatty's tintype tangle (1914) -- Fatty's new role (1915) -- Coney Island (1917).
VHS format.
Title on original container: Fatty Arbuckle festival.
Music sound track added.
Keywords: Comedy films; Short films; Silent films; Motion pictures -- History